Case Series of Potential Cardiac Inflammation Associated With Various SARS-CoV-2 Vaccinations Assessed by Cardiac MRI - Jahnke, Constantin; Doeblin, Patrick; Tanacli, Radu; Witt, Undine; Schneider, Matthias; Stehning, Christian; Pieske, Burkert; Kelle, Sebastian (Frontiers in Cardiovascular Medicine, 2022)
Serious adverse events associated with new vaccines targeting SARS-CoV-2 are of high interest to the public and to public health as a worldwide mass immunization campaign has been initiated to contain the ongoing COVID-19 pandemic. We describe a series of 4 individuals with signs of a myocarditis/pericarditis according to cardiac MRI results in temporal association with currently in the European Union authorized SARS-CoV-2 vaccines. We found mild abnormal MRI results independent of the type of SARS-CoV-2 vaccine. There is a need of continuing monitoring outcomes of myocarditis cases after COVID-19 vaccination as recently published cases suggest an uncomplicated short-term course whereas the long-term implications are not yet known but taking the available evidence into account the benefits of using COVID-19 vaccines still clearly outweigh the risks.